Redescription of Gessyella latridopsis (Johnston et Mawson, 1945) (Nematoda: Capillariidae), a parasite of latrid fishes from the southern hemisphere - Rossin, María Alejandra; Timi, Juan Tomás (Folia parasitologica, 2009)
The type species of the monotypic genus Gessyella Freitas, 1959, G. latridopsis (Johnston et Mawson, 1945) (Nematoda: Capillariidae), is redescribed from specimens found in the rectum of the marine fish Nemadactylus bergi Norman (Latridae, Perciformes) (a new host record) from the southwestern Atlantic Ocean off Mar del Plata, Argentina. In addition to the morphological and biometrical variability of this species, some new, previously unreported taxonomic features, such as the extent of the spination of the spicular sheath, the morphology of the spicular canal, the distal end of the spicule, the ejaculatory duct, the cloaca, the seminal vesicle, vas deferens and the testis, are described for the first time. Despite the long geographical distance of G. latridopsis records (Australia vs. Argentina), the morphology of the newly collected specimens is in agreement with the existing descriptions of G. latridopsis and both host species are closely related. Therefore, the Argentine specimens are considered to belong to this species.
Keywords: Oceans and Seas; Nematoda; hlístice; Argentina; Animals; oceány a moře; zvířata; Perciformes